2009
DOI: 10.1183/09031936.00196408
|View full text |Cite
|
Sign up to set email alerts
|

Myeloid RelA regulates pulmonary host defense networks

Abstract: The pulmonary innate immune system in the respiratory tract eliminates inhaled pathogens. Several cell types contribute to host defense within a complex network. The aim of this study was to evaluate the role of macrophages during pneumonia and in the regulation of the epithelial response to microorganisms.We performed lung infection models in mice lacking myeloid RelA/p65. To study the mechanistic relationships between individual cell types, we applied co-culture models composed of airway epithelial cells (AE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
29
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 44 publications
2
29
0
1
Order By: Relevance
“…Previous studies showed that TLR3 is expressed in primary respiratory epithelial cells and that TLR3 stimulation activates the IFN-b signaling pathways (34). We used Aspergillus extract instead of hyphae and conidia in our study and found that IFN-b signaling plays an important role as a target in the mechanism of IP-10 suppression by Aspergillus extract.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that TLR3 is expressed in primary respiratory epithelial cells and that TLR3 stimulation activates the IFN-b signaling pathways (34). We used Aspergillus extract instead of hyphae and conidia in our study and found that IFN-b signaling plays an important role as a target in the mechanism of IP-10 suppression by Aspergillus extract.…”
Section: Discussionmentioning
confidence: 99%
“…The protocol was approved by the Institutional Review Board (ethics committee) of the Saarland University Hospital, and informed consent was obtained from the patients. Lungs of mice were embedded in paraffin, and immunohistochemistry was performed as described earlier (2). FOXO3 was detected with primary Abs (anti-FOXO3A; Abcam) diluted 1:200 in TBS (13 PBS [pH 7.2], 0.1% BSA).…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…Some of these functions are constitutively active. However, in case of infection, epithelial cells directly detect pathogen-associated molecular patterns (PAMPs) in a pattern recognition receptor-dependent manner, resulting in enhanced innate immune responses (2,3,5). In addition, inflammatory cytokines (e.g., IL-1b and IL-17) released by professional immune cells induce innate immune functions of airway epithelial cells (6,7).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, in recent years, it has become evident that the epithelial surface of the respiratory tract not only provides a physical barrier that is highly effective in blocking penetration by most microbes but also has the ability to recognise microbes and to initiate an immune response [8,9]. Similar to classical immune cells, such as macrophages or neutrophils, respiratory epithelial cells are known to express a variety of pattern recognition receptors, including TLRs and NOD-like receptors (nuclear oligomerisation domain), allowing for the detection of diverse AFFILIATIONS *Dept of Internal Medicine, Division for Pulmonary Diseases, Universitätsklinikum des Saarlandes, Homburg, pathogens, such as bacteria and viruses [10]. Even though innate immune functions of respiratory epithelial cells are well described in the response to bacteria and viruses, little is known about the response of these cells to fungal pathogens such as A. fumigatus and its spores, the conidia.…”
mentioning
confidence: 99%